Gender and educational achievement: Stylized facts and causal evidence - Judith Delaney; Paul J Devereux (University College Dublin, UCD Centre for Economic Research, 2021)
There are two well-established gender gaps in education. First, females tend to have higher educational attainment and achievement than males and this is particularly the case for children from less advantaged backgrounds. Second, there are large differences in the fields of specialization chosen by males and females in college and even prior to college and females disproportionately enter less highly paid fields. This review article begins with these stylized facts and then moves on to describe evidence for the role of various factors in affecting educational achievement by gender. Gender differences in non-cognitive traits, behaviour, and interests have been shown to relate to differences in educational outcomes; however, this evidence cannot generally be given a causal interpretation. In contrast, the literature has been creative in estimating causal impacts of a wide range of factors using experimental and quasiexperimental variation. While the approaches are compelling, the findings vary widely across studies and are often contradictory. This may partly reflect methodological differences across studies but also may result from substantial true heterogeneity across educational systems and time periods. The review concludes by evaluating what factors are most responsible for the two central gender gaps, whether there is a role for policy to reduce these gender differences, and what the findings imply about the capacity for policy to tackle these gaps.
hdl:10197/11915
Keywords: I24; J16; 330; Education; Gender; Schools; Gender gaps; Gender and educational achievement; Gender and STEM